As memórias de futuro dos discursos apocalípticos da revista Superinteressante - Pugliese, Allan Tadeu (Universidade Federal de São Carlos, 2013)
This paper seeks indications of how discourses of science are transmitted to society and even to find ideological confrontations between these two discursive forces. For this the chosen corpus was constituted from the texts of the Superinteressante magazine, and the main concepts used to support this work were the dialogical theory, memories of the future, the incompleteness and the valuation of aesthetic Bakhtin. We will also use Leon (1999), who shows us the ways and history of scientific discourse. Thus we have as hypotheses of how this discourse is constructed, how it is valued and how it also serves to entertain and inform. We also use old speeches about the apocalypse, as the Holy Bible, the Mayan prophecies and the prophecies of Nostradamus to turn the discourse of the magazine historical discourses, seeking thereby modeling common to apocalyptic discourse. Thus, it seeks to relate all these concepts with the main problem: how language mediates to change the perception of science and society.
The Future memories of discourse apocalyptic at Superinteressante Magazine
Keywords: Linguística; Memória - futuro; Divulgação científica; Bíblia N.T. - Apocalipse - história; Bakhtin, Mikhail Mikhailovitch, 1895-1975; Discurso apocalíptico; História Apocalíptica; Jornalismo científico; Apocalyptic Discourse; Apocalyptic History; Scientific Diffusion; Scientific journalism; Mikhail Bakhtin; LINGUISTICA, LETRAS E ARTES::LINGUISTICA